The Role of Interventional Radiology in the Management of Pancreatic Pathologies - Ghali Salahia; Sook Cheng Chin; Ian Zealley; Richard D. White (Thieme Medical and Scientific Publishers Pvt. Ltd., 2020)
Pancreatic pathologies are varied and wide-ranging, and a multidisciplinary approach is essential for effective diagnosis and management. We describe image-guided percutaneous (nonendoscopic) interventions in the management of pancreatic disease, with emphasis on inflammatory and neoplastic pancreatic pathologies and on the transplanted pancreas. Image-guided treatments for the complications of pancreatitis include percutaneous interventions on simple and complex peripancreatic collections, pseudocysts, and fistulas. Vascular interventions predominantly focus on the treatment of pseudoaneurysms, hemorrhagic pseudocysts, and arteriovenous malformations. Emerging ablative techniques for pancreatic cancer are promising and include percutaneous radiofrequency ablation, microwave ablation, irreversible electroporation, and electrochemotherapy. Image-guided interventions on the transplanted pancreas commonly include percutaneous biopsy and drainage in addition to endovascular treatments of vascular complications.